Representations of Space and “Restoring Order” in Peter Eschenloer’s Wrocław Chronicle - Čapský, Martin (My University, 2022)
The author analyses Peter Eschenloer’s Wrocław Chronicle from the second half of the fi fteenth century. His interpretations are based on the theory of the relationship between power, space and representation. The Wrocław chronicler simultaneously defended the denial of the city’s obedience to the Bohemian king (who was in dispute with the pope) and condemned the riots provoked by the city’s municipality. The key part of the German-language version of Eschenloer’s chronicle takes place during a period when the town council faced a series of attacks to its authority. Eschenloer presents the reader with a “representation of (dis)order” in the form of the breakdown and disunity of the town and its consequences, laying groundwork that enables him to emphasize the legitimacy of the town councillors’ actions and present the bounds of their authority as inclusive of all public space.
Reprezentace prostoru a obnova "řádu" ve Vratislavské kronice Petra Eschenloera
Keywords: Silesia; Late Middle Ages; Wrocław; Urban historiography; City Council and Municipality; Central Europe; Peter Eschenloer.; Slezsko; pozdní středověk; Vratislav; urbánní historiografie; městská rada a obec; střední Evropa; Petr Eschenloer